2004
DOI: 10.1002/hipo.10167
|View full text |Cite
|
Sign up to set email alerts
|

Encoding versus retrieval of spatial memory: Double dissociation between the dentate gyrus and the perforant path inputs into CA3 in the dorsal hippocampus

Abstract: The hippocampus is an essential neural structure for spatial memory. Computational models suggest that the CA3 subregion of the hippocampus plays an essential role in encoding and retrieval of spatial memory. The perforant path (PPCA3) and dentate gyrus (DG)-mediated mossy fibers (MFs) compose major afferent inputs into CA3. A possible functional dissociation between these afferent inputs was attempted using a simple navigation test (i.e., the modified Hebb-Williams maze). Behavioral testing was combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
176
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 230 publications
(217 citation statements)
references
References 28 publications
(43 reference statements)
22
176
4
2
Order By: Relevance
“…Given the observed selective deficits in retrieval of spatial cues necessary for navigation of a maze and previous evidence implicating CA1 in retrieval (Hasselmo, 1995;Hasselmo et al, 1995;Sybirska et al, 2000;Kesner et al, 2004;Lee and Kesner, 2004b;Jerman et al, 2006;Rolls and Kesner, 2006), we reasoned that similar selective deficits may be apparent in additional CA1-dependent tasks. It has been shown previously that CA3-lesioned rats are significantly impaired on the acquisition, but not retention of contextual fear-conditioning whereas, CA1 lesioned rats are significantly impaired on retention but not acquisition (Lee and Kesner, 2004a).…”
Section: The Effects Of Apomorphine On Acquisition Of Contextual Fearmentioning
confidence: 94%
See 3 more Smart Citations
“…Given the observed selective deficits in retrieval of spatial cues necessary for navigation of a maze and previous evidence implicating CA1 in retrieval (Hasselmo, 1995;Hasselmo et al, 1995;Sybirska et al, 2000;Kesner et al, 2004;Lee and Kesner, 2004b;Jerman et al, 2006;Rolls and Kesner, 2006), we reasoned that similar selective deficits may be apparent in additional CA1-dependent tasks. It has been shown previously that CA3-lesioned rats are significantly impaired on the acquisition, but not retention of contextual fear-conditioning whereas, CA1 lesioned rats are significantly impaired on retention but not acquisition (Lee and Kesner, 2004a).…”
Section: The Effects Of Apomorphine On Acquisition Of Contextual Fearmentioning
confidence: 94%
“…Encoding of information acquired in a Hebb-Williams maze or in contextual fear conditioning, using a within-days analysis, is impaired by targeted lesions to the CA3 and dentate gyrus (DG) subregions, but not from targeted lesions to the CA1 subregion. In contrast, using a between-days analysis, retention and retrieval is disrupted following CA1, but not following CA3 or DG lesions (Lee and Kesner, 2004a;Lee and Kesner, 2004b;Jerman et al, 2006). Impairments have also been demonstrated in delay-dependent retrieval without impairing immediate recall or encoding of spatial information after infusing glutamatergic antagonists (Lee and Kesner, 2002), or cyclooxygenase-2 inhibitors (Sharifzadeh et al, 2006) into the CA1 subregion, but not when infused into the CA3 subregion.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recent experimental evidence supports this theoretical hypothesis. Lee and Kesner (2002) manipulated the N-methyl-Daspartate (NMDA) receptors in CA3 by injecting APV (amino-5-phosphonovaleric acid, a pharmacological blocker for the NMDA receptors) selectively into CA3 in a delayed non-matching-toplace (DNMP) task. They found that rats injected with APV were not impaired in performing the DNMP task in a familiar environment in which they had been trained.…”
mentioning
confidence: 99%